2017
DOI: 10.1103/physrevd.95.115009
|View full text |Cite
|
Sign up to set email alerts
|

Searches for new physics at the Hyper-Kamiokande experiment

Abstract: We investigate the ability of the upcoming Hyper-Kamiokande (Hyper-K) neutrino experiment to detect new physics phenomena beyond the standard, three-massive-neutrinos paradigm; namely the existence of a fourth, sterile neutrino or weaker-than-weak, non-standard neutrino interactions. With both beam-based neutrinos from the Japan Proton Accelerator Research Complex (J-PARC) and atmospheric neutrinos, Hyper-K is capable of exploring new ranges of parameter space in these new-physics scenarios. We find that Hyper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 109 publications
2
23
0
Order By: Relevance
“…In the present work, we focus on the proposed experiment Tokai to Hyper Kamiokande (T2HK), which will make use of a very powerful neutrino beam shot from Tokai to Kamioka over a distance of 295 km. Our work complements other recent studies performed about DUNE [11][12][13][14][15] and T2HK [15][16][17][18]. Previous studies on sterile neutrinos at LBL experiments can be found in [19][20][21][22][23][24][25][26][27].…”
Section: Introductionsupporting
confidence: 87%
“…In the present work, we focus on the proposed experiment Tokai to Hyper Kamiokande (T2HK), which will make use of a very powerful neutrino beam shot from Tokai to Kamioka over a distance of 295 km. Our work complements other recent studies performed about DUNE [11][12][13][14][15] and T2HK [15][16][17][18]. Previous studies on sterile neutrinos at LBL experiments can be found in [19][20][21][22][23][24][25][26][27].…”
Section: Introductionsupporting
confidence: 87%
“…Comparing these results with other sensitivity studies performed in the literature, for experiments such as Hyper-Kamiokande [41,42] or MINOS+ [43,44], one can see that the experimental setups proposed here look very promising indeed, especially for constraining sin 2 2θ μe .…”
Section: B Sensitivity To Light Sterile Neutrinos At An Lbnf Near Desupporting
confidence: 55%
“…For a given set of neutrino and antineutrino oscillation parameters, we compute the expected number of signal and background events as a function of energy for the experiment of interest, as outlined in more detail in [49,50] for DUNE † and Ref. [32] for Hyper-K. More concretely, we generate expected signal and background yields for the following experimental oscillation channels:…”
Section: Analysis Methodsmentioning
confidence: 99%
“…As opposed to DUNE, Hyper-K will spend more time collecting data in the antineutrino mode, with a run-time-ratio of 1 : 3 neutrino to antineutrino mode. We simulate the atmospheric muon neutrino samples by inflating the atmospheric neutrino sample of Super-Kamiokande to correspond to ten years of data collection with a detector twenty times larger [32].…”
Section: Analysis Methodsmentioning
confidence: 99%